PENGARUH PENDIDIKAN AGAMA ISLAM DAN BUDAYA RELIGIUS SEKOLAH TERHADAP KECERDASAN EMOSIONAL PESERTA DIDIK DI MI BATUNADUA KOTA PADANGSIDIMPUAN - Siregar, Linda Erawati (DIRASATUL IBTIDAIYAH, 2023)
Factors that influence and determine the emotional intelligence of students in life include Islamic religious education. Islamic religious education can create a main personality in which there is a creed that is firmly rooted so that the faith that is in him is strong, carries out worship continuously and istiqomah so that he can do charity sincerely and has good morals as an application of faith and charity so that he can achieve the degree of ihsan. In addition to Islamic religious education, students' emotional intelligence can also be influenced by the religious culture of the school. School religious culture is a tradition in inculcating Islamic behavior formed by the school environment as a routine that is realized in the form of worship. The type of research used is quantitative research while the information needed by researchers is obtained directly from the research object by distributing questionnaires to respondents. Data collection techniques used by researchers are questionnaires (questionnaires), documentation, and interviews. The analysis technique used is the validity and reliability test of the instrument then the data analysis used is the basic assumption test, the classic assumption test and the hypothesis test using the data processing computer program SPSS 22. The results showed that there was an influence of Islamic religious education on the emotional intelligence of Batunadua Ibtidaiyah Madrasah students, Padangsidimpuan City. There is the influence of the school's religious culture on the emotional intelligence of students at Madrasah Ibtidaiyah Batunadua, Padangsidimpuan City. The conclusion is that Islamic religious education and school religious culture simultaneously and partially influence the emotional intelligence of students at Madrasah Ibtidaiyah Batunadua, Padangsidimpuan City. Keywords: Islamic Religious Education; School Religious Culture; Emotional Intelligence.